The Influence of Human Resource Quality, Organizational Commitment, and Work Motivation on Employee Performance at Two Medan Madya Tax Services Offices - Hasibuan, Nurul Febriyana Luhty; Bangun, Mira Srinina; Martunis; Mirza, Teuku; Pane, Sri Gustina; Rahayu, Sri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to assess the impact of human resource quality, organizational commitment, and work motivation individually and collectively on employee performance at the Medan Moderate Tax Service Office. The research was conducted at the Medan Transitional Tax Service Office, located at Jalan Sukamulia No. 17A, Medan, with a population of 117 and a research sample of 54 individuals. Data collection involved interviews, surveys, and documentation. The IBM Statistics for Product and Service Solution (SPSS) version 24 was utilized for data analysis, employing multiple regression analysis. The findings of the study reveal that the quality of human resources significantly influences the performance of employees at the Medan Dua Intermediate Tax Service Office. This is supported by the results of the t-test analysis (3.894 > 2.009) at n = 54 with a 95% level of significance. Organizational commitment also impacts the performance of employees at the Medan Two Intermediate Tax Service Office, as indicated by t-test > t-table analysis (2.861 > 2.009) at n = 54 with a 95% level of significance. Similarly, work motivation affects the performance of employees at the Medan Two Moderate Tax Service Office, with t-test > t-table results (5.751 > 2.009) at n = 54 and a 95% level of significance. Furthermore, the F-test results (F-count > F-table) indicate that collectively, there is a positive and significant influence of human resource quality, organizational commitment, and work motivation on the performance of employees at the Medan Intermediate Tax Service Office (31.463 > 2.79).